2021
DOI: 10.3390/su13179598
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Degree of Balance between Urban and Tourism Development: An Analytical Approach Using Cellular Data

Abstract: This study presents an analytical approach for measuring the degree of balance between urban and tourism development, which has been previously analyzed qualitatively and was difficult to measure. With the help of 1012 million cellular data records generated by 20 million users in two weeks, we tracked the behavior of residents, commuters, and tourists at a set of historical conservation areas in central Shanghai. We calculated the degree of balance and visualized it via ternary graphs. Moreover, the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Studies on urban tourism focus on the relationship between tourism and cities, particularly the impact of tourism on cities [30,31]. On the one hand, tourism can promote urban economic development and infrastructure construction and improve the employment rate, which are positive effects [32].…”
Section: Literature Review: Toward An Innovative Framework Of Tomeci ...mentioning
confidence: 99%
“…Studies on urban tourism focus on the relationship between tourism and cities, particularly the impact of tourism on cities [30,31]. On the one hand, tourism can promote urban economic development and infrastructure construction and improve the employment rate, which are positive effects [32].…”
Section: Literature Review: Toward An Innovative Framework Of Tomeci ...mentioning
confidence: 99%
“…Researchers have examined the connection between tourism development and urban-rural areas [7][8][9]. From the urban perspective, researchers have primarily focused on the economic implications, spatial revitalization, regional disparities, and resident perceptions of the urban area as influenced by the tourism industry [10][11][12]. For instance, Ma et al [13] revealed that the rise in tourism significantly impacts China's urban economic growth without exacerbating economic disparities among cities.…”
Section: Introductionmentioning
confidence: 99%